Dendritic and Core–Shell–Corona Mesoporous Sister Nanospheres from Polymer–Surfactant–Silica Self‐Entanglement. Issue 2 (4th December 2017) - Zhang, Kun; Yang, Tai‐Qun; Shan, Bing‐Qian; Liu, Peng‐Cheng; Peng, Bo; Xue, Qing‐Song; Yuan, En‐Hui; Wu, Peng; Albela, Belén; Bonneviot, Laurent
Abstract: Mesoporous nanospheres are highly regarded for their applications in nanomedicine, optical devices, batteries, nanofiltration, and heterogeneous catalysis. In the last field, the dendritic morphology, which favors molecular diffusion, is a very important morphology known for silica, but not yet for carbon. A one‐pot, easy, and scalable co‐sol–gel route by using the triphasic resol–surfactant–silica system is shown to yield the topologies of dendritic and core–shell–corona mesoporous sister nanospheres by inner radial phase speciation control on a mass‐transfer‐limited process, depending on the relative polycondensation rates of the resol polymer and silica phases. The trick was the use of polyolamines with different catalytic activities on each hard phase polycondensation. The self‐entanglement of phases is produced at the {O −, S +, I − } organic–surfactant–inorganic interface. Mono‐ and biphasic mesoporous sister nanospheres of carbon and/or silica are derivatized from each mother nanospheres and called "syntaxic" because of similar sizes and mirrored morphologies. Comparing these "false twins", or yin and yang mesoporous nanospheres, functionalized by sulfonic groups provides evidence of the superiority of the dendritic topologies and the absence of a shell on the diffusion‐controlled catalytic alkylation of m ‐cresol. Abstract : Get in tune ! A variety of morphologies of polymer–surfactant–silica nanoparticles can be synthesized through easy and scalable syntheses, from which mono‐ or biphasic porous nanoparticles possessing different compositions, with similar size, shape, topology, and pore arrays, can be obtained (see figure). These ready‐made analogues are ideal to tune molecular diffusion limitation through the morphology.